Digital ecosystem in Guatemala - Nagaraji, Satish; Gardeazábal Monsalve, Andrea (International Food Policy Research Institute, 2022)
This technical brief provides an overview of the digital development gaps and challenges in Guatemala's agrifood systems. Based on the USAID Digital Ecosystem Framework, 323 actors across 14 types of organizations were identified as digital agrifood innovators in the country. In-depth assessments on challenges and opportunities were conducted on 50 select actors using a new survey instrument, Rapid Screening Tool. We find that Guatemala has a good mix of founders, technical resources, an educated workforce, and a growing tech industry. The government's substantial efforts toward digital society, rights, and data governance were remarkable. However, major challenges constraining digital ecosystems were weak digital literacy, inadequate infrastructure, and low affordability of digital technologies and solutions for both users and service providers in rural areas. We recommend specific actions for CGIAR to support partners in realizing the transformative potential of digital innovations.